2012
DOI: 10.1007/s00262-012-1343-0
|View full text |Cite
|
Sign up to set email alerts
|

Metronomic chemotherapy with low-dose cyclophosphamide plus gemcitabine can induce anti-tumor T cell immunity in vivo

Abstract: Several chemotherapeutic drugs have immune-modulating effects. For example, cyclophosphamide (CP) and gemcitabine (GEM) diminish immunosuppression by regulatory T cells (Tregs) and myeloid-derived suppressor cells (MDSCs), respectively. Here, we show that intermittent (metronomic) chemotherapy with low-dose CP plus GEM can induce anti-tumor T cell immunity in CT26 colon carcinoma-bearing mice. Although no significant growth suppression was observed by injections of CP (100 mg/kg) at 8-day intervals or those of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
78
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(85 citation statements)
references
References 32 publications
5
78
1
1
Order By: Relevance
“…Although they observed that cyclophosphamide therapy resulted in the preferential deletion of Treg cells, similar to previous studies, this therapy also enhanced the production of chronic inflammatory mediators by melanoma cells associated with an accumulation of Gr1+CD11b+ MDSCs. However, in a similar study of murine colon cancer, the ability of low-dose cyclophosphamide to promote MDSC expansion was reversed when low-dose gemcitabine was concurrently administered, resulting in reduced levels of MDSCs and potent antitumor immune responses [52]. This is consistent with a study by Suzuki et al demonstrating that gemcitabine (a single dose of 120 mg/kg) can selectively eliminate Gr1+CD11b+MDSCs in tumor-bearing mice [53].…”
Section: Treg/mdsc Modulation By Chemotherapeutic Drugssupporting
confidence: 84%
“…Although they observed that cyclophosphamide therapy resulted in the preferential deletion of Treg cells, similar to previous studies, this therapy also enhanced the production of chronic inflammatory mediators by melanoma cells associated with an accumulation of Gr1+CD11b+ MDSCs. However, in a similar study of murine colon cancer, the ability of low-dose cyclophosphamide to promote MDSC expansion was reversed when low-dose gemcitabine was concurrently administered, resulting in reduced levels of MDSCs and potent antitumor immune responses [52]. This is consistent with a study by Suzuki et al demonstrating that gemcitabine (a single dose of 120 mg/kg) can selectively eliminate Gr1+CD11b+MDSCs in tumor-bearing mice [53].…”
Section: Treg/mdsc Modulation By Chemotherapeutic Drugssupporting
confidence: 84%
“…85 Other reports, however, show that CTX induces early myeloid effector cells that may inhibit tumor cell growth through nitric oxide (NO) release, 86 and that metronomic CTX plus gemcitabine mitigates Treg-and MDSC-mediated immunosuppression and elicits antitumor immunity in vivo. 87 Among taxanes, paclitaxel specifically impairs viability and cytokine production in FOXP3 þ Treg cells, but not in FOXP3 À CD4 effector cells. 88 Docetaxel, another antimicrotubule agent, was shown to polarize MDSCs toward an M1-like phenotype, and to selectively kill MDSCs while sparing the M1-like cells.…”
Section: Effects On Regulatory Subsets and Pathwaysmentioning
confidence: 99%
“…As discussed below, this is consistent with the different locus of activity of each of these agents. Cyclophosphamide has been shown to mitigate Treg-mediated immunosuppression in rodents and in patients with cancer (34), as well as to promote immunogenic cell death and T cellmediated immunity (40). To determine combination effects with anti-SEMA4D, a suboptimal dose of cyclophosphamide was administered 1 day before immunotherapy.…”
Section: Tumor Growth Delay By Anti-sema4d Antibody Is Cd8mentioning
confidence: 99%